Greening EU competition law and policy - Kingston, Suzanne, 1977- (Cambridge : Cambridge University Press, 2012)
'One of the fundamental challenges currently facing the EU is that of reconciling its economic and environmental policies. Nevertheless, the role of environmental protection in EU competition law and policy has often been overlooked. Recent years have witnessed a shift in environmental regulation from reliance on command and control to an increased use of market-based environmental policy instruments such as environmental taxes, green subsidies, emissions trading and the encouragement of voluntary corporate green initiatives. By bringing the market into environmental policy, such instruments raise a host of issues that competition law must address. This interdisciplinary treatment of the interaction between these key EU policy areas challenges the view that EU competition policy is a special case, insulated from environmental concerns by the overriding efficiency imperative, and puts forward practical proposals for achieving genuine integration'--
Part I. Should Environmental Goals Play a Role in EU Competition Policy? -- Environmental protection in EU competition theory to date -- The rise of the market in EU environmental policy -- Why environmental protection goals should play a role in EU competition policy : a legal systematic argument -- Why environmental protection goals should play a role in EU competition policy : a governance argument -- Why environmental protection goals should play a role in EU competition policy : an economic argument -- Part II. The Role of Environmental Protection in EU Competition Policy in Practice -- Some preliminary issues : definition of an undertaking, market definition; effect on inter-state trade -- Article 101(1) TFEU -- Article 101(3) TFEU -- Article 102 TFEU -- EU merger policy -- The relevance of State action to Articles 101 and 102 TFEU -- State aid -- Part III. Conclusions.
Includes bibliographical references (p. 446-458) and index.
Keywords: Antitrust law -- European Union countries; Environmental law -- European Union countries